"Doesn't Anyone Believe How I Feel?": Postural Orthostatic Tachycardia Syndrome (POTS). (March 2015) - Uhrich, Alice E.; Hartung, Sheila Q.
The school nurse is often the first person with whom a student may discuss untoward health symptoms and concerns. Being cognizant of the clinical features of postural orthostatic tachycardia syndrome (POTS) will help the nurse alleviate some of the student's anxiety. Due to misunderstandings and misconceptions about POTS, family and peers may disbelieve a student who is experiencing symptoms. Displaying compassion and support will help the student understand that someone does believe his or her symptoms. As the student's advocate, the school nurse will champion a plan for the student's health and safety in the academic environment.